Determinantes de la deuda pública en Colombia durante 1990-2018 (2019)
The public debt of the Central National Government has presented increases in the last five years; and, being this one of the most relevant variables when analyzing the fiscal situation of a country, it is necessary to analyze the determinants of its behavior. Here, emphasis will be placed on macroeconomic factors and fiscal policy decisions, making use of econometric tools that allow us to explain the influence of those mentioned above.